The Effect of Corporate Social Responsibility Disclosure, Good Corporate Governance, and Intellectual Capital on Company Financial Performance with Company Size as a Moderating Variable - Novi Rahmadiah; Hafizh Fadhlurrahman; Michael Sahat (Journal of Applied Accounting and Sustainable Finance, 2026)
Purpose – This study investigates the financial performance of the non-cyclical consumer sector on the Indonesia Stock Exchange during the post-pandemic recovery and high-inflation period (2022-2024). It specifically examines the impact of Corporate Social Responsibility Disclosure (CSRD), Good Corporate Governance (GCG), and Intellectual Capital (IC) on Financial Performance, with Company Size as a moderating variable. Design/methodology/approach – This quantitative study analyzes a sample of 147 companies. Data were analyzed using panel data regression (Random Effects Model) processed through Eviews 9, moving away from previous inconsistencies regarding regression types. Findings – The analysis shows that CSRD and GCG have a negative and statistically insignificant effect on financial performance, indicating that governance structures and social disclosure in this sector have not been optimized for financial gain. Importantly, Intellectual Capital is found to have a negative and statistically significant effect on performance, indicating that high investment in intangible assets may act as a cost burden in the short term in this sector. However, Firm Size has a positive and significant direct effect on financial performance, reflecting economies of scale. Furthermore, although Firm Size fails to moderate the impact of CSRD and GCG, it significantly moderates and strengthens the relationship between Intellectual Capital and financial performance, implying that larger firms are better able to leverage intangible assets for value creation. Research limitations/implications – This study provides practical insights for managers in the consumer non-cyclicals sector to optimize their intellectual assets and reconsider the cost-benefit efficiency of CSR activities during the economic recovery phase. JEL : 14, M41, G34, O34, L25